2018
DOI: 10.20546/ijcmas.2018.708.055
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Ridge and Furrow System on the Growth and Yield Attribution of Soybean in Barwani District of M.P.

Abstract: The field experiment was conducted during the two consecutive Kharif season of 2011 and 2012 to study ridge and furrow in-situ conservation system for soybean crop at farmer's fields in Badwani district of Madhya Pradesh under Nimar agro-climatic region. Result showed that growth and yield contributing character viz. plant population, plant height, root length, root nodules, pods per plant, seed yield weight per plant, seed yield, straw yield and harvest index (%) found higher in ridge and furrow system compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
2
5
0
Order By: Relevance
“…The increment in biological yield under lower plant density might be due to higher radiation and light intensity interception over the canopy leading to higher leaf area, number of branches plant -1 , harvest index consequently causing higher biological yield. Interaction studies revealed that, 60 kg ha -1 seed rate with ridges and furrow sowing method showed a 29.58% increment of HI over control (70 kg ha -1 ) with flat bed sowing method, which conforms with Basediya et al [19] who reported that HI were found to be higher in ridge and furrow system as compared to flat bed sowing method. Higher HI under lower plant density might be due to maximum pods plant -1 and seed yield plant -1 due to exposure of plants to radiation and light leading to higher leaf area, more electron transport rate, photosynthetic activity, with efficient partitioning of photo assimilates towards pods or sink leading to higher Harvest index.…”
Section: Effect Of Seed Rate and Sowing Methods On Physiological Growth Determinants In Soybeansupporting
confidence: 84%
“…The increment in biological yield under lower plant density might be due to higher radiation and light intensity interception over the canopy leading to higher leaf area, number of branches plant -1 , harvest index consequently causing higher biological yield. Interaction studies revealed that, 60 kg ha -1 seed rate with ridges and furrow sowing method showed a 29.58% increment of HI over control (70 kg ha -1 ) with flat bed sowing method, which conforms with Basediya et al [19] who reported that HI were found to be higher in ridge and furrow system as compared to flat bed sowing method. Higher HI under lower plant density might be due to maximum pods plant -1 and seed yield plant -1 due to exposure of plants to radiation and light leading to higher leaf area, more electron transport rate, photosynthetic activity, with efficient partitioning of photo assimilates towards pods or sink leading to higher Harvest index.…”
Section: Effect Of Seed Rate and Sowing Methods On Physiological Growth Determinants In Soybeansupporting
confidence: 84%
“…Similar results were also reported by [25,26] . It reveals that higher net return of Rs 32920 per ha with B: C ratio of 3.35 is recorded in ridge and furrow system whereas, the lowest net return of 24660 per ha with and B: C ratio of 2.82 was recorded under normal flatbed sowing for year 2011 [6] .…”
Section: Effect Of Varieties and Crop Geometry In Yield Attributes And Yield Of Soybeanmentioning
confidence: 89%
“…In India, during 2000, its cultivation occupies an area of 12.2 million hectares with production was 89.19 lakh tones 2015-16 along with average productivity of 922 kg ha -1 2017-18 [5] . The crop experiences moisture stress during the dry spell ranging from 15 to 21 days at any growth stage under rainfed conditions, resulting significant reduction in the yield [6] . These yield losses are expected at higher level especially in early genotype with determinate types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean benefit cost ratio was (1.89) Narayana et al, (2011). andBasediya et al, (2018).In conclusion the agronomic measures for moisture conservation in rainfed Bt. cotton have significant influence on the growth, yield, productivity and economics among the various treatments.…”
mentioning
confidence: 85%